ECONOMIC EFFICIENCY AND BIOENERGETIC ASSESSMENT OF COMMERCIAL CROP PRODUCTION OF LETTUCE (LACTUCA SATIVA L. VAR. SECALINA ALEF.) - Dydiv , О.; Dydiv , І.; Sobotovych , М.; Stefkivska , Ю.; Zavalniuk , О.; Skubii , О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Due to the ongoing Russian-Ukrainian war, the consumption of fresh, marketable produce among the Ukrainian population is currently 6–7 times lower than the recommended dietary norms, exhibiting significant seasonal fluctuations. The shortage of ecologically safe, freshly harvested produce is especially acute during the autumn and winter months. Garden lettuce (Lactuca sativa L.), a fast-growing and cold-tolerant crop, allows for multiple sowing periods throughout the year and serves as an effective and efficient use of land on small plots. It can be cultivated as a precursor for thermophilic crops, as a catch crop, or as a post-harvest crop. At this stage of developing vegetable production infrastructure, consideration goes beyond just the nutritional value of a crop; it also includes the energy inputs required for its cultivation. Leafy greens, particularly garden lettuce, are classified as low-input crops. This species can be harvested from open fields in early spring, while greenhouse cultivation enables supply during winter and early spring. This study focused on garden lettuce (Lactuca sativa L.) cultivars of national selection: Snizhynka (control), Dublianskyi, Malakhit, and Zorepad. The authors assessed the economic efficiency and bioenergetic performance of marketable crop production under the conditions of the Western Forest-Steppe region of Ukraine. Throughout a three-year study period, the leaf-type cultivars examined yielded, on average, 2.20 to 4.56 t/ha more than the control cultivar, Snizhynka, when using the seedling cultivation method (pot-grown transplants). Economic evaluations of commercial production indicated that profitability levels were influenced by both the cultivation method and the specific cultivar. For Lactuca sativa var. secalina L. cultivars, profitability ranged between 86% and 130%. The cost of marketable produce utilizing the seedling method was found to vary from 746 to 963 UAH per ton. The bioenergetic assessment, which focused on specific elements of the cultivation technology, showed yields of 21.0 to 33.0 t/ha for pot-grown seedlings and 20.0 to 32.0 t/ha for plug tray seedlings. The bioenergetic efficiency coefficient for lettuce production during this study period ranged from 1.20 to 1.40, depending on the cultivation method employed.